Learners' Autonomy and Motivation: The Effect of Autonomy Supportive/Controlling Teachers on Students' Motivation - Safyah, Saad Suwyid (Eximia, 2022)
This paper sheds some light on the subject of learners' autonomy from three angles. The first is the relationship between the students' autonomy and their motivation; how high feeling of autonomy elevates their motivation. While, low feeling of autonomy diminishes the students' motivation. The second is the effect of the strategies and techniques that the teachers use to support or to control their students' autonomy on the learners' motivation. Moreover, the impact of the environment created by teachers to support/control the autonomy of the students on their motivation.